Oral Pathology in Clinical Dentistry: A systematic approach - R V Subramanyam (Wolters Kluwer Medknow Publications, 2014)
The dental clinician frequently comes across lesions that involve the hard and soft tissues of the oral cavity. Most of these conditions do not pose a diagnostic problem for the dental surgeon. However, the clinical dentist is sometimes accosted with a lesion, the diagnosis of which is not only challenging, but influencing the choice of treatment. This review article provides a systematic and logical approach for diagnosing common lesions encountered in the dental practice.